PROGNOSTIC FACTORS OF LEPTOSPIROSIS PATIENTS IN DR. SARDJITO GENERAL HOSPITAL, YOGYAKARTA, INDONESIA - Kurniaatmaja, E.R, Kurniaatmaja, E.R; Priambodo, Doni; Humardewayanti, Rizka; Loeheri, Soebagjo (Acta Interna The Journal of Internal Medicine, 2011)
Background: Leptospirosis, an infectious disease that affects humans and animals, is a common zoonosis with a variety of clinical manifestations. Yogyakarta is one of the cities with a high incidence of leptospirosis. It is important to recognize the clinical features and prognostic factors of this disease. Severe disease can be fatal, although majority of cases are mild and self-limited.Â Objective: To determine the prognostic factors for leptospirosis that associated with mortality in patients with leptospirosis in Dr. Sardjito General Hospital, Yogyakarta.Â Methods: We conducted a retrospective study of data collected in our hospital between Jan 2010 until May 2011, from whom the diagnosis of leptospirosis was confirmed based on pertinent clinical and epidemiological data and positive serology.Â Result: Thirty two patients were included in this study, including 29 survivors (90.62%) and 3 non-survivors (9.38%). Of these 32 patients, 26 patients (81.25%) were admitted to the medical ward and 6 patients (18.75 %) were admitted to the ICU.Â Multivariate logistic regression demonstrated that three factors were independently associated with mortality: oliguria (OR 0.75; CI 0.541â1.04; p<0.05); urea nitrogen > 74.7 mmol/L (OR 0.813; CI 0.642-1.028; p<0.05), and neurological symptoms (altered mentation or seizure) (OR 30; CI 4.367â206.07; p<0.05)Â Conclusion: The mortality of leptospirosis remains high despite improvements in patients care. In order to improve the early treatment of high-risk patients, these 2 clinical and 1 laboratory criteria which are associated with mortality, can be used at the time of admission as prognostic factors.Â Â Keywords : Leptospirosis, prognostic factors, mortality